“The Impact of Interactive Learning Methods on Students’ Critical Thinking in School Clubs” - Djabbarova Nargiza Bakitovna (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article investigates the impact of interactive learning methods on developing students’ critical thinking skills through school club activities. The study emphasizes how hands-on exercises, collaborative projects, and digital tools can enhance students’ analytical abilities, problem-solving skills, and independent thinking. The paper also discusses pedagogical strategies to maximize engagement and educational outcomes in extracurricular settings.